Biomodulatory Approaches to Photodynamic Therapy for Solid Tumors - Anand, Sanjay (2012)
Photodynamic Therapy (PDT) uses a photosensitizing drug in combination with visible light to kill cancer cells. PDT has an advantage over surgery or ionizing radiation because PDT can eliminate tumors without causing fibrosis or scarring. Disadvantages include the dual need for drug and light, and a generally lower efficacy for PDT versus surgery. This minireview describes basic principles of PDT, photosensitizers available, and aspects of tumor biology that may provide further opportunities for treatment optimization. An emerging biomodulatory approach, using methotrexate or Vitamin D in combination with aminolevulinate-based PDT, is described. Finally, current clinical uses of PDT for solid malignancies are reviewed.